The Depiction of Female Characters in Eugene O’Neill’s mourning Becomes Electra - Tarish, Zainab Hameed; Zainal, Zaidah Bt; Samat, Norhanim Bte Abdul (International Journal of Psychosocial Rehabilitation, 2020)
This study deals with Eugene O’Neill’s play entitled Mourning Becomes Electra (1931). The play tackles the tormented human soul and some of the modern serious psychological problems. O’Neill was aiming at reforming the American society by eradicating the evils that occurred due to the lack of morality. Along these lines, the present study is conducted to exhibit the depiction of female characters in one of the most dysfunctional and horrifying families in American literature. This research paper is concentrating on the factors that ruined the characters starting with betrayal, then murders and suicides, followed by karma. The researcher bases the paper depending on Thematic Analysis to exhaust the above mentioned themes and to portray the female characters who experience the majority of the excruciating circumstances which at last prompted the whole family’s breakdown. The findings demonstrate that the females are mentally tormented with remorse and sorrow because of their psychological issues and complexes, in addition to their actions. Since, their lives are filled with disgust and hatred towards each other, therefore karma haunts all of them eventually.